Development of communicative competence among plurilingual students in monolingual Croatian language practice - Pavličević-Franić, Dunja (Vestnik za tuje jezike, 2010)
When starting school pupils begin to adopt the standard Croatian language (non-dominant L2), which in some regions differs from the native idioms (dominant L1). In this situation the interlanguage field is created and most students become vertically plurilingual, i.e. the interweaving of different language codes is reflected in monolingual school practice. In this research the greatest attention has been paid to the cognitive-linguistic paradigm and the constructivist theory, within which the stimulus theory and error theory have proven to be an extremely purposeful part of the learning process in the early language development. The aim was to examine the purposefulness of the application of the modern learning theories on the development of communicative competence of younger primary school pupils. The research results have confirmed that communicative competence can be successfully developed, among other, by taking advantage of errors as a stimulus for further learning. Only in such a situation the interlanguage field in monolingual Croatian language practice should be treated as a positive and not a negative linguistic phenomenon.
Keywords: Croatian; hrvaščina; standardni jezik; sporazumevalna zmožnost; jezikovni razvoj; teorije učenja; osnovna šola; primary school; Hrvaška; Croatia